SOLID DISPERSION FOR INCREASING DISSOLUTION RATE OF SODIUM DICLOFENAC WITH VARIATIONS OF POLYVINYL PYRROLIDONE K30 - Noval, Noval; Rosyifa, Rosyifa (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2021)
Diclofenac sodium is included in class II category based on biopharmaceutics classification system (BCS), sodium diclofenac has low solubility and high permeability. Low solubility will affect absorption of drugs in body because rate of dissolution will decrease. PVP K30 is inert carrier that dissolves easily in water and can affect solubility of an active drug substance. To know solid dispersion system increasing dissolution rate of sodium diclofenac by adding variations concentration of PVP K30. Solid dispersion uses solvent method with variations concentration of PVP K30 1:3, 1:5, 1:7 and 1:9. Test physical properties of solid dispersions using a moisture test and compressibility. Solid dispersion dissolution test using type 2 dissolutions test and determination of concentration using UV-VIS spectrophotometry. Test results were analyzed using One Way ANOVA and continued test. Solid dispersion has a good physical whit moisture percentage not >5% and compressibility not >20%. Solid dispersion of sodium diclofenac with addition of PVP K30 can increase dissolution rate compared to pure sodium diclofenac (p<0,05) with highest at ratio 1:7. Each comparison has significant difference (p<0,05) expect in ratio 1:9. Solid dispersion of sodium diclofenac with PVP K30 can increase dissolution rate of pure sodium diclofenac.